Impaired regulation of heart rate and sinoatrial node function by the parasympathetic nervous system in type 2 diabetic mice - Yingjie Liu (Nature Portfolio, 2021)
Abstract Heart rate (HR) and sinoatrial node (SAN) function are modulated by the autonomic nervous system. HR regulation by the parasympathetic nervous system (PNS) is impaired in diabetes mellitus (DM), which is denoted cardiovascular autonomic neuropathy. Whether blunted PNS effects on HR in type 2 DM are related to impaired responsiveness of the SAN to PNS agonists is unknown. This was investigated in type 2 diabetic db/db mice in vivo and in isolated SAN myocytes. The PNS agonist carbachol (CCh) had a smaller inhibitory effect on HR, while HR recovery time after CCh removal was accelerated in db/db mice. In isolated SAN myocytes CCh reduced spontaneous action potential firing frequency but this effect was reduced in db/db mice due to blunted effects on diastolic depolarization slope and maximum diastolic potential. Impaired effects of CCh occurred due to enhanced desensitization of the acetylcholine-activated K+ current (IKACh) and faster IKACh deactivation. IKACh alterations were reversed by inhibition of regulator of G-protein signaling 4 (RGS4) and by the phospholipid PIP3. SAN expression of RGS4 was increased in db/db mice. Impaired PNS regulation of HR in db/db mice occurs due to reduced responsiveness of SAN myocytes to PNS agonists in association with enhanced RGS4 activity.